Kritik Sosial Natsume Soseki dalam Novel Bocchan - Oekon, Deddy Hernandy (Universitas Gadjah Mada, 2023)
This research aims to reveal Natsume Soseki's attitudes and views in the form of social criticism regarding the phenomenon of social deviation in Japanese society due to the Meiji Restoration (1868-1912) in his novel, Bocchan. Social problems often arise in modern societies, including what happened in Japan during modernization from 1868-1912, called the Meiji Restoration. These social problems include social and cultural dislocation due to the penetration of dominant Western culture and the marginal position of traditional elements, especially in the second decade of the early Meiji era, when Japan aggressively adopted Western culture on a large scale. This social phenomenon can be seen from the decline in Japanese society's appreciation for traditional social and cultural values while simultaneously placing Western culture in a superior position. The theory used in this research is Alan Swingewood's Literary Sociology theory. Through this theory, we will analyze the influence of Natsume Soseki's social background as the author of the novel Bocchan, as well as his ideological tendencies in responding to the symptoms of social deviation in Japanese society (1868-1912), which became the background for the creation of the novel Bocchan. After that, it will be analyzed to what extent the novel Bocchan can reflect social phenomena. The analysis was done by connecting the social aspects of the novel with the historical, social reality that was the background for its creation, namely Japanese society during the Meiji Era (1868-1912). Next, the author will see what social criticism is depicted in the novel. The results of the research show that the novel Bocchan describes Natsume Soseki's social criticism of the phenomenon of socio-cultural dislocation in Japanese society due to Westernization during the Meiji era, as well as the problems of a group of people who persist with old habits in the condition of the Japanese nation which is changing towards a developed and modern country.